Pemberian Bantuan Kartu Indonesia Pintar menggunakan Metode Weighted Product - Irmayanti, Hani; Gaffar, Abdul Majid (Computer Engineering Departement, Universitas Komputer Indonesia, 2023)
ABSTRACT – The purpose of this research is to determine which students meet the criteria for receiving assistance from the Indonesia Smart Card program, so that the aid can be targeted appropriately. The Indonesia Smart Card cannot be given to all financially disadvantaged students who meet the criteria, as the quota for the card is very limited. The method used in this study is the Weighted Product method. The Weighted Product method is a decision-making method that uses multiplication to connect attribute values, where each attribute must be raised to the power of the corresponding attribute weight. The results obtained from this study are the ranking of students who meet the predetermined criteria according to the specified quota. The ranking is obtained through the process of determining the criteria first, then determining the values for each alternative, improving the weights of the implemented criteria, calculating the s-vector, calculating the v-vector, and finally ranking. The conclusion of this study is that the student ranking process is in accordance with the available quota and can be carried out transparently, accountably, and objectively. The Student Affairs Office is greatly helped in making decisions, so that aid can be targeted more accurately. Keywords – Indonesia Smart Card; Weighted Product; Decision-making system; Assistance; Ranking